Efficacy and safety of pegylated interferon in the treatment of JAK2V617F-positive polycythemia vera with a dose de-escalation strategy: a single-center retrospective study - Chang, Long; Li, Wen-Xin; Cai, Hao; Li, Jian; Duan, Ming-Hui (Frontiers in Oncology, 2025)
IntroductionAlthough pegylated interferon (PEG-IFN) has been widely used in the treatment of polycythemia vera (PV), there is still a significant variability in its specific dosage and administration.MethodsThis single-center retrospective study assessed the efficacy and safety of PEG-IFN in JAK2V617F-positive PV patients using a dose de-escalation strategy.ResultsFrom 2018 to 2022, 110 PV patients received PEG-IFN treatment and monitored for JAK2V617F variant allele frequency (VAF) over 12 months, with 95.4% achieving complete hematological response (CHR) and 70.8% and 71.8% achieving molecular response (MR) according to the ELN2009 and 2013 criteria respectively. Patients with increased Immunoglobulin level after treatment seemed to have a higher MR rate according to the ELN2013 criteria, but the statistical difference was not significant. According to the 2013 criteria, patients with a baseline JAK2V617F VAF ≥75% had a significantly lower MR rate, and those who achieved MR had a significantly lower neutrophil-to-lymphocyte ratio (NLR) after 3 months of treatment. Although 98.2% patients experienced laboratory adverse events, only 6 patients stopping due to adverse reactions.DiscussionThe study found that initiating PEG-IFN at 180ug weekly and adjusting only for adverse events was well-tolerated and may offer superior outcomes to traditional dosing strategies. The 12-month hematological and molecular efficacy were promising, suggesting this approach has the potential to improve long-term survival in PV patients, although further research is needed to confirm these findings.